Soft tactile sensor to detect the slip of a Robotic hand. (15th August 2022) - Kim, Minsong; Yang, Junmo; Kim, Donghyun; Yun, Dongwon
Highlights: The sensor detects the force due to slip using the piezoresistive principle. The gap design of the sensor performs two kinds of axis decoupling. The sensor's silicone, a hyperelastic body, protects the sensor's internal structure. The sensor's reliability is confirmed with a drift of 0.204% in repeat experiment. A slip detection ability is confirmed in experiment using the fabricated gripper. Abstract: Robotic hands using tactile sensors are widely used in various industrial fields. Slip detection is important tactile information for stable gripping. In this paper, a soft tactile sensor that reliably pinches atypical objects by detecting slip is presented. The sensor can detect slip in two directions. The internal structure of the sensor was fabricated using a small strain gauge, and when slip occurs, the shear force is sensed by the piezoresistive principle. It is covered with silicone, a hyperelastic substance like human skin, and the sensor was designed to decouple the force in each axial direction analytically and experimentally. Additionally, its high durability and precision were confirmed through repeated experiments. The picking experiment using the fabricated gripper and sensor showed the sensor could detect slips on objects of various shapes, weights, and materials, and it is also possible to detect slips that occur additionally due to rotation and lifting speed.